MIKROENKAPSULASI EKSTRAK FORMULA PEGAGAN-KUMIS KUCING-SAMBILOTO SEBAGAI INHIBITOR Angiotensin I Converting Enzyme SECARA In Vitro - Rani, Ismarani; Pradono, Dyah Iswantini; Darusman, Latifah K (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2011)
Chitosan microencapsulation contained extract formula pegagan-kumis kucingsambiloto was resulted from ionic gelation process. Chitosan microencapsulation wasresulted by cleaning bath type of ultrasonication and homogenization methods. Optimum condition obtained at 2% of chitosan concentration (w/v) and 50 mL (v/v) of extract formula. The yields of chitosan microparticles was 64.24%. Characterization by SEM at 5000× magnification showed that the particle size of chitosan microparticles was not uniform. Chitosan microparticles without and contained extract formula had diameters between 0.40 μm-8.5 μm and 1 μm-6 μm, respectively. Each chitosan microparticles contained extract formula and extract formula had the ACE inhibitory activity of 78.41 %, and 75.73 %, respectively, while the captopryl as an positive control had ACE inhibitory activity of 75.24 %. Wave number peaks of chitosan spectrum was different with microparticles spectrum by using of FTIR analysis. Chitosan microparticles-sodium tripolyphosphate (STP) contained extract formula had absorbance bands of 1652.32 cm-1 (C=O) and 1565.63 cm-1 (C=C, aromatic group of benzene). New absorbance bands also appeared at wave numbers of 1153.82 cm-1 and 1154.66 cm-1 which showed absorbance band of P=O group from STP compound.